Quality of life measurement: bibliographic study of patient assessed health outcome measures. Issue 7351 (15th June 2002) - Garratt, Andrew; Schmidt, Louise; Mackintosh, Anne; Fitzpatrick, Ray
Abstract: Objectives: To assess the growth of quality of life measures and to examine the availability of measures across specialties. Design: Systematic searches of electronic databases to identify developmental and evaluative work relating to health outcome measures assessed by patients. Main outcome measures: Types of measures: disease or population specific, dimension specific, generic, individualised, and utility. Specialties in which measures have been developed and evaluated. Results: 3921 reports that described the development and evaluation of patient assessed measures met the inclusion criteria. Of those that were classifiable, 1819 (46%) were disease or population specific, 865 (22%) were generic, 690 (18%) were dimension specific, 409 (10%) were utility, and 62 (1%) were individualised measures. During 1990-9 the number of new reports of development and evaluation rose from 144 to 650 per year. Reports of disease specific measures rose exponentially. Over 30% of evaluations were in cancer, rheumatology and musculoskeletal disorders, and older people's health. The generic measures—SF-36, sickness impact profile, and Nottingham health profile—accounted for 612 (16%) reports. Conclusions: In some specialties there are numerous measures of quality of life and little standardisation. Primary research through the concurrent evaluation of measures and secondary research through structured reviews of measures are prerequisites for standardisation. Recommendations for the selection of patient assessed measures of health outcome are needed.